Evaluación de dos dietas alimenticias adicionando proteína y energía en el peso de lechones postdestete, Mira-Carchi - Guerrero Guerrero, Andrea Daniela (2022)
The general situation of low weight in weaning piglets is present in all pig farms\; therefore, in Ecuador it is not the exception, since it is a constant in modern productions. The main cause of the problem is the lack of knowledge of the fundamentals and knowledge necessary to supply a diet that meets the requirements of the animal at this stage. One option in the face of this problem is the use of food supplements that help the piglets not to lose weight and, in turn, help production. Thus, energy and protein supplements are an alternative with great potential in pig production to improve weight and feed conversion. The main objective of this research was to evaluate two diets with the addition of an energy and protein supplement for weight improvement in weaned piglets in Cantón Mira, Carchi province. The study consisted in the use of a statistical model (DCA) that consists of three treatments that were: T1 food plus the addition of an energy supplement (cane filter cake), T2 food plus the addition of a protein supplement (raw earthworm) and T3 only the balanced food without any nutritional supplement\; Subsequently, the supplements were added to the food by mixing, and a dose of food was given according to the number of animals present in each treatment. The benefits of the experience of said research were demonstrated through the records of weight performance, as well as the results of the feed conversion that consists of how many kilograms of food consumed for the gain of one kilogram of weight. The results show that the strategy in the use of food supplements (energy and protein), is an effective alternative for weight gain with averages of T2 23.68 kg, T1 26.26 kg and T3 22.74 kg and in terms of feed conversion T2 1.804, T1 2.275, T3 2.433 in piglet rearing.